Unfolding research themes for industrial symbiosis and underlying theories - Agudo, Fabiana Liar [UNESP]; Bezerra, Barbara Stolte [UNESP]; Gobbo, José Alcides [UNESP]; Paes, Luis Alberto Bertolucci [UNESP] (Wiley, 2022)
This paper aims to analyze the research themes that are addressed in studies on industrial symbiosis (IS), from the perspective of theories. The paper method is a longitudinal analysis of retrospective nature from 1998 to 2021. This approach allowed to detects the main drivers and associated themes that structured researches on IS in the period. In general, Industrial Ecology Theory, Network Theory, Systems Theory and Organizational Theory were present in a considerable part of research themes on IS. It was observed that the IS research themes moved over the period analyzed to nine areas of study: (1) Waste as a resource, (2) development industrial symbiosis network, (3) circular economy and industrial symbiosis, (4) industrial co-localization, (5) energy innovations, (6) closed loop chains, (7) IS's social aspects, (8) regional-level metabolism, and (9) waste knowledge. In summary, the contributions of this paper are the thematic proposition of IS from the perspective of theories, pointing out the key-aspects; and presentation of a research themes' diagram towards the IS buildup.
Keywords: circular economy; industrial ecology; longitudinal analysis; sustainable development; waste to value